Jurisdictional Boundaries in the Making: The Case of Parish Diaconal Work in Finland - Pyykkö, Raija; Henriksson, Lea; Wrede, Sirpa (Professions and Professionalism, 2011)
Diaconal workers of the Evangelical Lutheran Church of Finland have traditionally worked on the borderline between parish work and public welfare services. However, the role of parish diaconal workers in social services and nursing services has diminished as the Finnish welfare state has expanded. In conjunction with this downsizing, the so-called intra-church diaconate process has re-demarcated parish diaconal work. Andrew Abbott’s theory of how professional jurisdictions are negotiated in the societal arenas in which different actors are engaged inspired the analysis in this article. Using Thomas F. Gieryn’s concept of boundary work, the jurisdictional settlements that reshape professional parish diaconal work are examined. It is argued that institutional boundary work and disputes over whether the culture of diaconal work is secular or spiritual, serve to renew its cultural jurisdiction.